The Effectiveness of Human Resource Management Training on Increasing Cognitive Competence in the Field of Personnel in Students: Efektivitas Pelatihan Human Resource Management Terhadap Peningkatan Kompetensi Kognitif Bidang Personalia pada Mahasiswa - Sahira, Anes Nur Eva; Widyastuti, Widyastuti (Universitas Muhammadiyah Sidoarjo, 2023)
This study aims to determine the effectiveness of Human Resource Management training towards improving cognitive competence in the field of personnel for the psychology students 2018 UMSIDA. This research using pre-experiment method the type On Group Pretest-Posttest with the subject is 155 students. The measuring instrument used is an achievement test to determine the effectiveness of Human Resource Management training in the field of personnel based on Indonesian National Comptency Work Standards 2020. This study uses the test data analysis in the form of paired sample T-test to determine the increase in cognitive competence of students befor and after Human Resource Management training with JASP 0.16.3.0. Paired sample T-test results show a significant increase in cognitive competence, indicated by the value of t = -4.851, p < .001. Cohen’s d score shows the number 0.407 which means an increase in cognitive competence in psychology students 2018 Muhammadiyah University of Sidoarjo after attending the Human Resource Management training.